2020
DOI: 10.1097/sla.0000000000003266
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis on Omentoplasty for the Management of Abdominoperineal Defects in Patients Treated for Cancer

Abstract: The objective of this systematic review and meta-analysis was to examine the effects of omentoplasty on pelviperineal morbidity following abdominoperineal resection (APR) in patients with cancer. Background: Recent studies have questioned the use of omentoplasty for the prevention of perineal wound complications. Methods: A systematic review of published literature since 2000 on the use of omentoplasty during APR for cancer was undertaken. The authors were requested to share their source patient data. Meta-ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 48 publications
1
30
0
Order By: Relevance
“…In the current pilot study with its small sample size, we found no distinct improvement in perineal wound healing rate compared to recent literature on various closure techniques after APR [2, 7, 19]. In addition, when compared to outcomes from our institution (and two other hospitals) after APR with primary layered closure and pedicled omentoplasty, we observe similar wound healing rates [20].…”
Section: Discussionsupporting
confidence: 44%
“…In the current pilot study with its small sample size, we found no distinct improvement in perineal wound healing rate compared to recent literature on various closure techniques after APR [2, 7, 19]. In addition, when compared to outcomes from our institution (and two other hospitals) after APR with primary layered closure and pedicled omentoplasty, we observe similar wound healing rates [20].…”
Section: Discussionsupporting
confidence: 44%
“…In a recently published meta-analysis, it was found that omental transposition had no effect on wound healing [ 30 ]. Moreover, this meta-analysis reported omental transposition-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…If the OP appears to be of poor quality on postoperative imaging-due to for example partial necrosis-the outcomes appear to be even worse than not performing an OP. Furthermore, the protective effect in preventing small bowel obstruction remains speculative, and there is likely an elevated risk of developing a perineal hernia after OP if considering recent literature [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there seems a similar need for operative management of small Electronic supplementary material The online version of this article (https://doi.org/10.1007/s00384-019-03412-0) contains supplementary material, which is available to authorized users. bowel obstruction and even an increased risk of perineal herniation in patients who have had OP [9].…”
Section: Introductionmentioning
confidence: 99%